Nilai Kearifan Lokal Nyepi Segara Sebagai Modal Sosial Pembangunan Berkelanjutan Daerah Pesisir Nusa Penida - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Luh Adisti Abiyoga Wulandari; I Gede Putu Kawiana (Jurnal Penelitian Agama Hindu, 2022)
This study aimed to analyze the value of Nyepi Segara local wisdom as social capital in relation to the influence of community participation on sustainable development in the coastal area of ​​Nusa Penida. This study involved 100 respondents consisting of local communities, religious leaders, regional officials and tourism actors in Nusa Penida. This study uses Moderating Regression Analysis (MRA) with data collection using observations, interviews, and questionnaires. The results of this study indicate that community participation and social capital have a significant effect on sustainable development, where Nyepi Segara as social capital strengthens the influence of community participation on sustainable development. The novelty of this research is to explore the value of the local wisdom of Nyepi Segara as a social capital that influences community participation in sustainable devlopment.